Highly active and durable nitrogen doped-reduced graphene oxide/double perovskite bifunctional hybrid catalysts - Kim, Nam-In; Afzal, Rana Arslan; Choi, Sung Ryul; Lee, Sung Won; Ahn, Docheon; Bhattacharjee, Satadeep; Lee, Seung-Cheol; Kim, Jung Hyun; Park, Jun-Young (ROYAL SOC CHEMISTRY, 2017)
A-site cation doping in perovskite-based materials with the general ABO(3) formula has a significant effect on the bifunctional oxygen activity (oxygen evolution and reduction reactions) of chemically stable electrocatalysts, enabling the design of highly active, durable, and cost-effective catalysts. In particular, the oxygen activity of double perovskite-structured NdBa0.5Sr0.5Co1.5Fe0.5O5+delta (NBSCF) is 0.973 V, which is much greater than that of previously reported transition metal-based nanostructures. This result is verified by examination of the electronic structure, oxidation state, and electrical properties of the perovskite-based materials using density functional theory (DFT) calculations, the iodometric titration method, X-ray photon spectroscopy (XPS), and electrochemical impedance spectroscopy (EIS) analysis. Further improvements of NBSCF for bifunctional oxygen activity are made by incorporating these synergistic hybrid structures with nitrogen doped-reduced graphene-based (N-rGO) nanostructures (NBSCF/N-rGO). The NBSCF/N-rGO has an oxygen electrode activity of 0.766 V, which is superior to that of other previously reported transition metal-based nanostructures and compares favorably to that of precious metal electrocatalysts. Furthermore, strong N-rGO provides considerably greater electrochemical long-term stability and integrity to NBSCF/N-rGO hybrid catalysts under continuous chronopotentiometric and long-term potential sweep testing conditions for the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR).
Keywords: OXYGEN-REDUCTION; COBALT OXIDE; FUEL-CELLS; ELECTROCATALYTIC ACTIVITY; WATER OXIDATION; METAL-FREE; IN-SITU; EVOLUTION; AIR; CARBON